Epidemiological Trends of Human Monkeypox Cases in Northern, Southern, Western, and Eastern Regions in Europe: A Cross-Sectional Study - Sultan Ayoub Meo; Abdulaziz Hassan Alsomali; Abdullah Abdulrahman Almushawah; Anusha Sultan Meo (Journal of Tropical Medicine)
Background. The growing amount of monkeypox cases in non-endemic regions raises concerns in societies as a potential pandemic. This study highlights the prevalence and epidemiological trends of a human monkeypox outbreak in various regions in Europe. Methods. This cross-sectional study was conducted in the Department of Physiology, College of Medicine, King Saud University, Riyadh, Saudi Arabia. The data about the monkeypox outbreak in European countries were recorded by the World Health Organization (WHO), and Centers for Disease Control and Prevention (CDC) reports. The period prevalence-based data were recorded from Jan 1, 2022, to July 7, 2022, and analyzed, and epidemiological trends were established in different European regions and countries. Results. In Europe, the human monkeypox rapidly spread in all the four subregions and involved 30 European countries, infecting 6077 people. The rising number of monkeypox cases is identified in Western Europe, 2599 (42.76%); Southern Europe, 1932 (31.79%); Northern Europe, 1487 (24.46%); and Eastern Europe, 59 (0.97%). In Western Europe, significant cases are found in Germany (1304), France (604), the Netherlands (352), Belgium (168), and Switzerland (131). In Northern Europe, it is found in the United Kingdom (1351), Ireland (44), Sweden (28), and Denmark (26); in Southern Europe, it is found in Spain (1256), Portugal (415), and Italy (233). However, a smaller number of cases are found in Eastern European states, Hungary (22), Poland (13), and Romania (12). The results further revealed that the number of monkeypox cases per million people in Northern Europe was 14.40%; Southern Europe, 13.49%; Western Europe, 13.26%; and Eastern Europe, 0.70%. The highest monkeypox cases per million population are found in Portugal, 40.70; Gibraltar, 29.68; Spain, 26.86; the United Kingdom, 19.90; Malta, 18.12; the Netherlands, 20.54; Germany, 15.56; Switzerland, 15.14; Belgium, 14.50; France, 9.27; and Ireland, 8.90. Conclusions. In a short period, the monkeypox cases swiftly spread in 30 non-endemic European countries and involved all four European regions. The healthcare authorities must take timely decisions to control the outbreak of human monkeypox disease, as the world cannot afford the global burden of human monkeypox outbreak as another potential pandemic.